STRUCTURAL AND DYNAMIC ANALYSIS OF SOCIAL RESPONSIBILITY OF HIGHER EDUCATION INSTITUTIONS IN THE CONTEXT OF STRATEGIC MANAGEMENT - Яценко, Валентина (Journal of Strategic Economic Research, 2022)
The article highlights the issues of structural and dynamic analysis of social responsibility of higher education institutions in the context of strategic management. The growing importance of ethical behavior and the strategic vector of society's development, aimed at spreading the concept of corporate social responsibility, encourages higher education institutions to pay more attention to principles and values aimed at ensuring the appropriate level of educational and social problems. The need to include elements of social responsibility in the strategic management of higher education institutions is explained by their ability to influence various interest groups and the ability to promote social development. The social responsibility of a higher education institution in the context of strategic management should be seen as a policy of continuous improvement in order to effectively fulfill its social mission through various areas of governance: organizational, educational, social and social. The article highlights the possibility of expanding the potential of higher education institutions to influence stakeholders through the use of social responsibility tools in strategic management. The strategic decisions of higher education institutions influence a variety of stakeholders in the organizational, educational, scientific and social spheres, and the importance of this issue also stems from the idea that higher education institutions are an important link in the well-being of society. Thus, the only way to increase the value of social responsibility for higher education institutions is through its integration into strategic management. The mission, goals and specific strategic actions must meet the needs and expectations of stakeholders, as well as coordinate the whole process, using the strategic plan as a management tool.